Ouvidorias públicas federais: Análise dos elementos que contribuem para a promoç\~ao da gest\~ao social - Ronald do Amaral Menezes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Social management is presented as a counterpoint to the strategic management to the extent that its dialogic nature promotes participation and sharing of decisions. In this context, in the midst of the Brazilian re-democratization process, emerge instances and mechanisms of social participation, among which stand out the public ombudsman in the promotion and defense of rights, valuation of citizenship, and improving of public management. This study aims to present and discuss elements that contribute to the federal ombudsman offices to play their part in strengthening social management in Brazil, through an autonomous action, which induces social participation and promote societal accountability processes.
Keywords: H83; 330; social management; strategic management; managerial public administration; societal public administration; federal ombudsman offices; participation and social control